Long-term outcomes of symptomatic and asymptomatic patients undergoing carotid endarterectomy in an average-volume community hospital. Issue 6 (2nd November 2021) - Alvarez Gallesio, José M.; Ruiz, Patricio Gimenez; David, Michel; Devoto, Martin; Caride, Alejandro; Borracci, Raúl A.
Abstract: Background: Long-term benefit of carotid endarectomy has not yet been fully investigated in average volume centers. Thus our purpose is to evaluate long-term results of carotid endarterectomies at a medium-volume hospital. Methods: A retrospective analysis of carotid artery stenosis operated between 2008 and 2017 in a community hospital was done. Demographic and postoperative outcomes were evaluated in short and long-term by Kaplan–Meier survival analysis. Results: 167 procedures in 159 patients were included. Average age was 72 years, and 65% were men. Twenty-nine percent of the patients were symptomatic and the rest asymptomatic. Median hospitalization was 3 (IQR 3–4) days and the mean follow-up was 56 months. No hospital mortality was recorded. At 120-month follow-up, freedom of stroke was 97.4%, death 97.3%, restenosis, 98.7% and all combined events 92.9% (log rank p = .042) Combined event-free survival was 84.4% in symptomatic patients, and 96.1% in asymptomatic patients (log rank p = .025). Conclusions: In a medium-volume hospital combined event-free survival was 84.4% in symptomatic patients and 96.1% in asymptomatic at a 10-year follow-up.